Fußballlinguistik als Forschungsbereich der Sportlinguistik – Neue wissenschaftliche Perspektiven - Jakub Dzidek (Linguistische Treffen in Wrocław)
The reviewed article discusses the book ,,Reingegrätscht. Eine kleine Linguistik des Fußballs‘‘ by Simon Meier-Vieracker (eds.). The introductory part mentions the role of sport, especially football, in today’s society, which requires and justifies research in all its areas. Language is an important aspect of the whole phenomenon, which for various reasons manifests itself not only within the sports environment. In the next section, attention is given to the motivations and research areas of the articles, which cover a range of consensual situations (Internet, language of fans, language of commentators, women’s football, etc.). However, those that provide a new overview of the issue seem particularly important. As a result, they are discussed in detail, which allows appropriate conclusions to be drawn later. The concluding section presents both the evaluation and the potential further research topics that can be found after reading the volume.